US policy towards research joint ventures: Special issue on science and technology policies towards research joint ventures - Nicholas S. Vonortas (Fondazione Eni Enrico Mattei (FEEM), 2000)
The US government has decidedly moved towards encouraging co-operation in research and development (R&D) between firms, universities, and other research institutes since the early 1980s. The Republican Administration in the early 1980s set the stage for a radical shift in market environment affecting business strategy and behaviour, including the undertaking of co-operative R&D, by introducing extensive changes in antitrust and intellectual property rights law and enforcement. These changes weakened competition policy and significantly strengthened IPR protection. Moreover, a series of legislative actions created the legal framework for promoting industry-university-government co-operation in science and technology and for allowing industry and universities to benefit financially from the results of research funded by the federal government The Democratic Administrations in the 1990s further built on this system, largely by pushing forward a series of Programmes actively promoting government-industry-university partnerships and trying to "channel" private sector R&D activity in technological areas with potentially widespread economic returns. While many of the specific S&T programmes have since been scaled down by Congress, the general policy orientation towards closer collaboration between industry, universities, and government has remained intact.
Keywords: O3; L4; L5; 330; Technology policy; R&D co-operation; research joint ventures; Forschungskooperation; Europäische Forschungs- und Technologiepolitik; Konzentrationspolitik; Immaterialgüterrechte; USA